Epigenetic Switch Driven by DNA Inversions Dictates Phase Variation in Streptococcus pneumoniae. - Jing Li; Jing-Wen Li; Zhixing Feng; Juanjuan Wang; Haoran An; Yanni Liu; Yang Wang; Kailing Wang; Xuegong Zhang; Zhun Miao; Wenbo Liang; Robert Sebra; et al. (PLoS Pathogens)
DNA methylation is an important epigenetic mechanism for phenotypic diversification in all forms of life. We previously described remarkable cell-to-cell heterogeneity in epigenetic pattern within a clonal population of Streptococcus pneumoniae, a leading human pathogen. We here report that the epigenetic diversity is caused by extensive DNA inversions among hsdSA, hsdSB, and hsdSC, three methyltransferase hsdS genes in the Spn556II type-I restriction modification (R-M) locus. Because hsdSA encodes the sequence recognition subunit of this type-I R-M DNA methyltransferase, these site-specific recombinations generate pneumococcal cells with variable HsdSA alleles and thereby diverse genome methylation patterns. Most importantly, the DNA methylation pattern specified by the HsdSA1 allele leads to the formation of opaque colonies, whereas the pneumococci lacking HsdSA1 produce transparent colonies. Furthermore, this HsdSA1-dependent phase variation requires intact DNA methylase activity encoded by hsdM in the Spn556II (renamed colony opacity determinant or cod) locus. Thus, the DNA inversion-driven ON/OFF switch of the hsdSA1 allele in the cod locus and resulting epigenetic switch dictate the phase variation between the opaque and transparent phenotypes. Phase variation has been well documented for its importance in pneumococcal carriage and invasive infection, but its molecular basis remains unclear. Our work has discovered a novel epigenetic cause for this significant pathobiology phenomenon in S. pneumoniae. Lastly, our findings broadly represents a significant advancement in our understanding of bacterial R-M systems and their potential in shaping epigenetic and phenotypic diversity of the prokaryotic organisms because similar site-specific recombination systems widely exist in many archaeal and bacterial species.